Adverse reaction to metal debris after Birmingham hip resurfacing arthroplasty. (4th May 2015) - Junnila, Mika; Seppänen, Matti; Mokka, Jari; Virolainen, Petri; Pölönen, Tuukka; Vahlberg, Tero; Mattila, Kimmo; Tuominen, Esa K J; Rantakokko, Juho; Äärimaa, Ville; Itälä, Ari; Mäkelä, Keijo T
Abstract : Background and purpose — Concern has emerged about local soft-tissue reactions after hip resurfacing arthroplasty (HRA). The Birmingham Hip Resurfacing (BHR) was the most commonly used HRA device at our institution. We assessed the prevalence and risk factors for adverse reaction to metal debris (ARMD) with this device. Patients and methods — From 2003 to 2011, BHR was the most commonly used HRA device at our institution, with 249 implantations. We included 32 patients (24 of them men) who were operated with a BHR HRA during the period April 2004 to March 2007 (42 hips; 31 in men). The mean age of the patients was 59 (26–77) years. These patients underwent magnetic resonance imaging (MRI), serum metal ion measurements, the Oxford hip score questionnaire, and physical examination. The prevalence of ARMD was recorded, and risk factors for ARMD were assessed using logistic regression models. The mean follow-up time was 6.7 (2.4–8.8) years. Results — 6 patients had a definite ARMD (involving 9 of the 42 hips). 8 other patients (8 hips) had a probable ARMD. Thus, there was definite or probable ARMD in 17 of the 42 hips. 4 of 42 hips were revised for ARMD. Gender, bilateral metal-on-metal hip replacement and head size were not factors associated with ARMD. Interpretation — We found that HRA with the Birmingham Hip Resurfacing may be more dangerous than previously believed. We advise systematic follow-up of these patients using metal ion levels, MRI/ultrasound, and patient-reported outcome measures.